Fabrication, In Vitro and In Vivo Evaluation of Non-Ordered Mesoporous Silica-Based Ternary Solid Dispersions for Enhanced Solubility of Flurbiprofen - Muhammad Usman Munir; Mahnoor Ikraam; Muhammad Nadeem; Syed Haroon Khalid; Sajid Asghar; Ikrima Khalid; Muhammad Irfan; Nayyer Islam; Nyla Ajaz; Ikram Ullah Khan (Pharmaceuticals, 2022)
The aim of this study was to improve the solubility and prevent the ulcerogenic effect of flurbiprofen. Initially, binary and ternary solid dispersions (BSDs and TSDs) of flurbiprofen were prepared by using non-ordered mesoporous silica and gelucire. After preformulation testing (solubility, flow properties, % yield, and entrapment efficiency), four formulations were selected for further detailed studies. Solid-state characterization of optimized formulations (S1, S6, S7, and S12) showed successful drug incorporation in the solid dispersion at the molecular state without any noticeable interactions. The in vitro solubility and release study showed an increase in solubility and 98–100% of drug release in 30–45 min. The in vivo gastro-protective effect of the optimized formulations containing flurbiprofen and silica (1:1) with 25% w/w gelucire (S6 and S12) showed a reduction in the gastric lesion index (GLI) after four days of treatment. Moreover, histological images of the stomach lining (S6 and S12) illustrated normal epithelial cells and a partially protected mucosal membrane. Thus, TSD exhibited a significant increase in solubility and the dissolution rate and reduced the gastric ulceration. Therefore, TSDs are dubbed as efficacious carriers to enhance the bioavailability of flurbiprofen while simultaneously reducing its side effects.